Psychological and other correlates of academic performance in medical students at a tertiary care hospital: A Cross-sectional study - Priyanka Semwal; Ranjeeta Kumari; Vikram Singh Rawat; Nisarg Aravindan; Anushikha Dhankar (Indian Journal of Community Medicine, 2022)
Background: High percentage of medical students showed multiple psychological factors that may interfere with their academic performance and identifying the problems in early stage and providing them advice is very important for their mental health. Methodology: The study targeted undergraduate medical students studying at All India Institute of Medical Sciences, Rishikesh, Uttarakhand, India. Selected students completed the self-administered questionnaire comprising the psychological correlates such as perceived stress scale, Pittsburgh sleep quality index, ten-item personality inventory, and other correlates such as sociodemographic and scholastic characteristics. The association of these psychological and other correlates with academic performance was analyzed using the Chi-square test at P >0.05. Results: Students with poor sleep quality 60.2% and 57.1% of students had high-stress levels perform well in academics. 70.2% of girls and 64.5% of general category students performed well in academics. Student's family head having a professional degree was associated with good performance in academics 64.3%. Moreover, students belonging to the upper class (69.2%) performed better. No significant association was observed between psychological correlates with academic performance but observed between sociodemographic and scholastic variables with academic performance. Conclusion: Among undergraduate medical students, there was no significant association of psychological correlates such as stress level, sleep quality, and anxiety trait with academic performance.